Why the Estates? Hans Ulrich's Recovery of an Unpopular Notion - Brock, Brian (Studies in Christian ethics, 2007)
This paper outlines Hans Ulrich's reworking of the Lutheran doctrine of the estates. He conceives the estates as descriptions of the new patterns of social life that God has promised to found and secure. This emphasis on the divine activity of generating social order is an expression of Ulrich's agreement with common and familiar criticisms of the doctrine, and why he nevertheless believes it indispensable for an evangelical ethic. A construal of the traditional doctrine of the estates that is unique even in his native Lutheran context, it aims not at conservatism, but at a more thoroughly theological and therefore critical relationship to social order than rival theories much more inclined to revisionist rhetorical stances. In a contemporary context in which moral certainties and categories can be disputed at the most fundamental levels, Ulrich's theology seeks a form of theological reasoning that genuinely seeks the illumination of Christian beliefs about reality by taking other moral languages seriously.